Research of Electric/Diesel Hybrid on Rail Heavy-duty Track Maintenance Machine - XU Jianming (机车电传动)
Dual-power sourced rail heavy-duty track maintenance machines were proposed against the defects of the current diesel engine and hydraulic-driven mode. The advantages and application range of the electric/diesel hybrid on rail heavy-duty track maintenance machine were analyzed, and the technical difficulties were described. Finally, a brief introduction of electric/diesel hybrid 48-stones rail grinding machine was provided.